Discontinuous deformation analysis based on strain-rotation decomposition. (February 2017) - Fan, Huo; Zheng, Hong; Zhao, Jidong
Abstract: The S-R (strain-rotation) decomposition theorem has an ability to capture strain components and rotation components at the same time. Using the principle of virtual power (VP), in this study, a new formulation independent of specific numerical methods is proposed for the analysis of dynamic large or small deformation. Then, the formulation is applied to the discontinuous deformation analysis (DDA), yielding a new DDA based on the S-R decomposition theorem, abbreviated as SRDDAvp . Compared with the conventional DDA, SRDDAvp adopts a slightly modified basic variables together with the generalized- α method. The analysis of some typical examples indicates that SRDDAvp can naturally overcome the issue of volume expansion, effectively improve the calculation accuracy and, equip DDA with the potential to treat large deformation. Highlights: A dynamics calculation formulation based on the S-R decomposition is deduced first using the principle of virtual power. An update process for the co-moving coordinate, which is closely related to the S-R decomposition, is detailed. The new formulation is applied to discontinuous deformation analysis (DDA) in order to establish S-R-based DDA. The new DDA can naturally overcome the issue of volume expansion and can effectively improve the calculation accuracy.